Ferroptosis in diabetic cardiomyopathy: from its mechanisms to therapeutic strategies - Tian, Meimei; Huang, Xinli; Li, Min; Lou, Pingping; Ma, Huijie; Jiang, Xinli; Zhou, Yaru; Liu, Yan (Frontiers in Endocrinology, 2024)
Diabetic cardiomyopathy (DCM) is defined as structural and functional cardiac abnormalities in diabetes, and cardiomyocyte death is the terminal event of DCM. Ferroptosis is iron-dependent oxidative cell death. Evidence has indicated that iron overload and ferroptosis play important roles in the pathogenesis of DCM. Mitochondria, an important organelle in iron homeostasis and ROS production, play a crucial role in cardiomyocyte ferroptosis in diabetes. Studies have shown some anti-diabetic medicines, plant extracts, and ferroptosis inhibitors might improve DCM by alleviating ferroptosis. In this review, we systematically reviewed the evidence of ferroptosis in DCM. Anti-ferroptosis might be a promising therapeutic strategy for the treatment of DCM.